Health systems science education: The new post-Flexner professionalism for the 21st century. (8th April 2021) - Borkan, Jeffrey M.; Hammoud, Maya M.; Nelson, Elizabeth; Oyler, Julie; Lawson, Luan; Starr, Stephanie R.; Gonzalo, Jed D.
Abstract: The foundations of medical education have drawn from the Flexner Report to prepare students for practice for over a century. These recommendations relied, however, upon a limited set of competencies and a relatively narrow view of the physician's role. There have been increasing calls and recommendations to expand those competencies and the professional identity of the physician to better meet the current and future needs of patients, health systems, and society. We propose a framework for the twenty-first century physician that includes an expectation of new competency in health systems science (HSS), creating 'system citizens' who are effective stewards of the health care system. Experiential educational strategies, in addition to knowledge-centered learning, are critically important for students to develop their professional identity as system citizens working alongside interprofessional colleagues. Challenges to HSS adoption range from competing priorities for learners, to the need for faculty development, to the necessity for buy-in by medical schools and their associated health care systems. Ultimately, success will depend on our ability to articulate, encourage, support, and evaluate system citizenship and its impact on health care and health care systems.